Ethical Implications Of Artificial Intelligence In Healthcare Decision-Making A Crossroads Of Social Values, Computer Algorithms, And Medical Practice. - Vinu, W.; Patra, Purnendu Kumar; Lakshman, Katam Naga; Bhattacharjee, Ripon; Baruah, Dilip Kumar; Chutia, Bhaskar Jyoti; Das, satish Kumar (Journal of Namibian Studies)
The progression of Artificial Intelligence (AI) is poised to revolutionize healthcare, augmenting human expertise with computational capabilities to transform clinical decision-making. This study delves into the intricate dynamics among societal values, computational algorithms, and medical practice, shedding light on the juncture where AI functions as a collaborative tool, elevating diagnostic precision and treatment selection while upholding the human dimension in patient care. The evolution of AI technology highlights its capacity to process extensive medical data, unveiling nuances imperceptible to human observation. Nevertheless, the assimilation of AI within clinical contexts prompts ethical considerations concerning the continuity of patient-centric care. The essence of patient provider relationships—characterized by empathy and emotional resonance—intersects with AI's computational efficacy. This inquiry navigates this intersection by exploring models of collaboration that harmonize AI with human judgment, enriching clinical accuracy while honoring the complexities of human experience. In response to the dynamic healthcare landscape, various dimensions come into focus, spanning the augmentation of diagnostic precision to the intricate intricacies of treatment selection. These facets underscore the symbiotic rapport between AI algorithms and human expertise. Nonetheless, challenges emerge in the integration process—ensuring AI's transparency, preserving patient autonomy, and addressing potential erosion of trust. This work underscores the essential equilibrium between AI's capabilities and the essence of compassionate human care. By traversing diagnostic accuracy, treatment selection, and the preservation of human attributes, this study embarks on a holistic exploration. It navigates the metamorphosis of medical practice, steered by AI-augmented healthcare. This investigation illuminates the trajectory toward an ethically grounded, patient centric integration of AI, heralding a transformative era in healthcare while honoring the timeless principles of empathetic care.